Corporate Governance Mechanisms on Earnings management in the Indonesian Banking Sector - Abraham Dwi Wicaksono; Maria Goreti Kentris Indarti; Jacobus widiatmoko (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to examine the influence of corporate governance on earnings management. The corporate governance variable is proxied by independent commissioners, audit committees, and audit quality. The data in this research is secondary data originating from the financial reports of banking companies listed on the Indonesia Stock Exchange in 2019-2022. Design/methodology/approach: The analytical techniques used to test the hypothesis in this research are descriptive statistics, classical assumption tests, and multiple linear regression analysis. The type of data used in this research is quantitative data. The sample for this research was obtained using a purposive sampling method, and a sample of 116 banking companies was obtained. Research Findings: Test results using multiple linear regression show that the independent commissioner variable does not affect earnings management. the audit committee variable has negative impact on earnings management while audit quality variable have a significant positive effect. Test results also show that the control variable ROA has a significant negative influence on earnings management (EM). However, the leverage control variable does not influence management (EM). Theoretical Contribution/Originality: This research contributes by providing nuanced insights into the specific impact of corporate governance components on earnings management within Indonesian banking companies. The findings offer a deeper understanding of the intricate relationships between governance mechanisms and financial practices. Research limitation and implication: Limitations include the focus on banking companies and the specific time frame. Future research may explore diverse sectors and extend the study period. The results imply the need for policymakers and practitioners to recognize the varying impacts of different corporate governance components on earnings management for effective financial oversight.